A Critical Analysis of Offset Agreements and Technological Innovation in Brazilian Defense Industrial Base - Rober, Yamashita (2020)
Offset agreements are claimed to enhance technological innovation in defense industrial base (DIB). This thesis aims to investigate the relationship between offset agreements and technological innovation in Brazilian DIB. Literature reveals that the topic offset agreements is controversial when a technological innovation approach is taken in consideration and the results are country specific. Brazilian Ministry of Defense offset agreements policy is new, having started in 2000’s and with a considered budget to be invested in equipment purchase in the next years. The research was conducted by using mixed methodology combining quantitative and qualitative data, both collected and analyzed at the same time. Quantitative data were obtained with an adapted questionnaire distributed to national defense industrial base and analyzed using Partial Least Squares method. A new model, able to measure the relationship between offset agreements and technological innovation, was developed and tested. Interviews with key informants provided the qualitative data that was coded and analyzed with NVivo software. The results of the study shows that from both analysis, five indicators (co-production, licensed production, subcontracted production, investments and technology transfer) were considered significant to offset agreements related to technological innovation in DIB for Brazil’s context. These results contribute to the theory of offset agreements providing a measurable model related to technological innovation, and have implications to practice including Brazilian DIB and policy makers. It was concluded that offset agreements have a positive relationship with technological innovation in Brazilian DIB and technology transfer is one of the main contributors to this.